Influence of the scatter of strength and of measurement uncertainties on the determination of the subcritical crack growth exponent in ceramics and glasses. Issue 4 (April 2017) - Krautgasser, C.; Bermejo, R.; Supancic, P.; Danzer, R.
Abstract: Subcritical crack growth (SCCG) in glasses and ceramics causes a decrease of strength with time under applied load. The dependence of the crack growth rate with the stress intensity factor can be approximated by a power law, with n being the SCCG exponent. In this work the effect of the inherent scatter of strength as well as measurement uncertainties on the determination of n is analysed. Constant stress rate tests as proposed in the EN 843-3 standard are simulated using Monte Carlo techniques. It is shown that the large scatter of strength causes large uncertainties on the determination of n, yielding a significant influence of the sampling procedure especially for small samples. Measurement uncertainties have a surprisingly low influence on the determination of n with exception of a special situation that may arise during long time testing campaigns.